Dolnośląskie szkolnictwo wyższe jako pracodawca na regionalnym rynku pracy - Popiński, Krzysztof (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
One of the most significant aspects of European integration is the process of creation of the European Higher Education Area. Higher education in Poland, which participates in the process from the beginning of the 1990's, undergoes a rather sudden transformation. As the result of the development of the existing schools as well as the appearance of new ones, the possibilities of higher education are now bigger than before. The overall number of students grew almost four times and the growth in the percentage of students among young people has been the same. The growth of the number of extramural and evening students has been significant. It favours the development of education in its multilevel and continual character. The choice of specializations is wider and better adapted to the current economic needs and job-market conditions. Polish higher schools are trying to continually intensify their participation in international cooperation, including student exchange. The participation in the multilateral EU programmes has been dominant in this respect. These changes are in line with the development of Poland strategy requirements and the commitments related to Poland's accession to the Bologna Process.What is worrying and even negative, however, is that the development of higher education in Poland rests on the development of simple quantitative rather than qualitative factors. For instance, the growth of the number of schools and students is not accompanied by the growth of the number of teachers. It aggravates, often considerably, conditions for improvement in the quality of teaching and even for development of science in general. Non-state schools do not help to improve the situation, as they have not managed to constitute a competitive force for state schools. As far as the student exchange is concerned, a worrying phenomenon is the disproportion between constantly growing number of Polish students at schools in Western Europe and a small number of foreign students coming to study in Poland. Overcoming these negative phenomena seems to be at present the most important task in the development of Polish higher education and its integration with the European Union. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 106-115